Responsiveness of electromyographically assessed skeletal muscle inactivity: methodological exploration and implications for health benefits - A. J. Pesola; Y. Gao; T. Finni (Scientific Reports, 2022)
Abstract Prolonged sedentary behaviour is detrimental to health due to low contractile activity in large lower extremity muscle groups. This muscle inactivity can be measured with electromyography (EMG), but it is unknown how methodological factors affect responsiveness longitudinally. This study ranks 16 different EMG inactivity thresholds based on their responsiveness (absolute and standardized effect size, responsiveness) using data from a randomized controlled trial targeted at reducing and breaking up sedentary time (InPact, ISRCTN28668090). EMG inactivity duration and usual EMG inactivity bout duration (weighted median of bout lengths) were measured from large lower extremity muscle groups (quadriceps, hamstring) with EMG-sensing shorts. The results showed that the EMG inactivity threshold above signal baseline (3 μV) provided overall the best responsiveness indices. At baseline, EMG inactivity duration of 66.8 ± 9.6% was accumulated through 73.9 ± 36.0 s usual EMG inactivity bout duration, both of which were reduced following the intervention (−4.8 percentage points, −34.3 s). The proposed methodology can reduce variability in longitudinal designs and the detailed results can be used for sample size calculations. Reducing EMG inactivity duration and accumulating EMG inactivity in shorter bouts has a potential influence on muscle physiology and health.